The human nature: Divinity of man in IBN Arabi's and Shankara's perspectives - Sayari, Saeideh; Mamat, Mohd Zufri; Hasbullah, Maisarah (Primrose Hall Publishing Group, 2019)
Arabi's school of thought and Shankara's worldview have much in common. One of issue on which the two thinkers agreed is the divine nature of the human being. This paper compares the approach of the two figures in the issue through discussing and explaining the unity of Being/Reality and the identity of One Being/Reality and human nature. The concept of imago Dei in Ibn Arabi's works and the concept of Self in Vedanta will be debated. In contrast to Shanakra, for Ibn Arabi, the human self is considered as a reality and it has the stronger elements when the human being actualizes the divine attributes, especially knowledge. © 2019, Primrose Hall Publishing Group.